1985
DOI: 10.1038/bjc.1985.198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a radioimminoassay for neuron specific enolase in small cell lung cancer

Abstract: Summary A radioimmunoassay for neuron specific enolase (NSE), a marker of neuroendocrine differentiation, has been evaluated in small cell lung cancer (SCLC). In untreated patients 25/38 (68%) with localized SCLC had raised blood levels of NSE (>13 ng ml-1), in extensive disease 34/39 (87%) patients had raised NSE levels. In patients with non-small cell lung cancer (NSCLC) the serum levels were raised in 16/94 (17%). In extensive tumours of non-pulmonary origin NSE levels were increased in 24/116 (20%) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0
4

Year Published

1986
1986
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(51 citation statements)
references
References 18 publications
5
42
0
4
Order By: Relevance
“…In the meantime several reports have confirmed their results (5 -14). However i t became evident that patients with small cell lung carcinoma s well s patients with non-small cell lung carcinoma may exhibit high concentrations of γ-enolase in plasma or serum (3)(4)(5)(6)(7)(8)10). These results, confirmed by our measurements, possibly reflect some uncertainties in the exact histological classification, caused by mixed type carcinomas (24)(25)(26).…”
Section: Discussionsupporting
confidence: 71%
“…In the meantime several reports have confirmed their results (5 -14). However i t became evident that patients with small cell lung carcinoma s well s patients with non-small cell lung carcinoma may exhibit high concentrations of γ-enolase in plasma or serum (3)(4)(5)(6)(7)(8)10). These results, confirmed by our measurements, possibly reflect some uncertainties in the exact histological classification, caused by mixed type carcinomas (24)(25)(26).…”
Section: Discussionsupporting
confidence: 71%
“…Haemolysed samples were not used because they have been shown to be a cause of serum NSE increase (Cooper et al, 1985).…”
mentioning
confidence: 99%
“…The median level is significantly higher in patients with extensive than limited disease (P <0.001). Although 12.5 ng ml' is quoted as the upper limit of the normal range, it has been suggested that 25 ng ml-' is the clinically relevant level (Cooper et al, 1985;Esscher et al, 1985) and hence NSE concentrations are shown separately for values between 12.5 and 25 ng ml-'. Most patients with limited disease have levels in this range.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have shown that serum NSE is elevated in the majority of patients with extensive SCLC and a significant proportion of those with limited disease (Carney et al, 1982;Johnson et al, 1984;Akoun et al, 1985;Cooper et al, 1985;Esscher et al, 1985). Despite reports that NSE levels are consistently higher in extensive than limited stage SCLC, data on the prognostic value of NSE are limited (Akoun et al, 1985;J0rgensen et al, 1988).…”
mentioning
confidence: 99%